The dynamics of international organization in assisting children of poor local communities. - Fernandez, Myra May R.
This study examined the local programs for children in Iloilo and Antique funded by UNICEF and World Vision. It describes the kind of aid assistance provided by these organizations to children in the local communities. It also probes the underlying factor sand dynamics in the relationship between these foreign donors and the local beneficiaries. The roles of local partners in selecting beneficiaries and dispensing benefits as well as the challenges encountered during the implementation of the programs are explored. This also compares the UNICEF and World Vision's process beneficiaries and the way these organizations implement their programs., The participants of the study were the program administrators of UNICEF in PPDO-Antique and its administrators in Barangay Funda Dalipe, San Jose de Buenavista, Antique as well as World Vision-RSAI, Inc. program aministrators in Iloilo City, and its implementer in Barangay Sto. Niogono Norte, Arvalo City. Three sets of questionnaires were utilized in this study. The first set was intended for Worl Vision; and the second set was for Provincial Planning and Development Office of Antique and Rising Sun Association of Iloilo, Incorporated and; The third set was for the local partners in the barangay, the Barangay Council for the Protection of Children and United Norte for the children's Future. The findings showed that there were differences in the dynamics of UNICEF and World Vision terms of selecting community, children beneficiaries, and local partners. These organizations also differ in terms of program priority and type of donors. These differences can be traced back to the nature of these organizations. The partners of UNICEF and World Vision also vary in their functions as the local partner of World Vision sets the criteria in the selection of its beneficiaries contrary to that of the UNICEF.